BUILDING TRAJECTORY DATA WAREHOUSE TO SUPPORT TRAJECTORY CLUSTERING - Logianto, Albert
The development of tools that can track the location of objects such as GPS causes the number of spatio-temporal data to continue to increase. Spatio-temporal data is data that has attributes of space and time. Moving objects data is one example of spatio-temporal data. Examples of moving objects data are taxi movements in a city and animal migration movements. The growth of the number of spatio-temporal data is also followed by the need to analyze the data. One analysis that can be done is trajectory data mining. There are several types of tasks in trajectory data mining, one of which is trajectory clustering. Trajectory data warehouses can be used to support task clustering tasks. However, there are currently not many data warehouses that can support this specific requirement.